2006
DOI: 10.1007/s10353-006-0269-1
|View full text |Cite
|
Sign up to set email alerts
|

Laparoskopisch assistierte Appendektomie

Abstract: Zusammenfassung. Grundlagen: Die akute Appendizitis ist die häufigste kinderchirurgische Indikation.Methodik: Fallbericht über die erste Einzel-TrokarLaparoskopie-assistierte extrakorporale Appendektomie in Kroatien.Ergebnisse: Bei dieser Technik wird der Appendix über den Arbeitsport herausgezogen und die Resektion vor der Bauchdecke durchgeführt. Analog zu publizierten Daten ist unsere Erfahrung mit der Technik sehr gut, auch mit gutem kosmetischem Ergebnis.Schlussfolgerungen: Die Erfahrung mit der neuen min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…In this case series of 14 patients, the conversion and complication rates were similar to those reported by Valla et al [7], but the operating times were longer, averaging 87.5 min. Other authors have reported similar results [5,15,50,[56][57][58][59][60][61][62][63][64][65][66].…”
Section: Role In General Surgerysupporting
confidence: 80%
“…In this case series of 14 patients, the conversion and complication rates were similar to those reported by Valla et al [7], but the operating times were longer, averaging 87.5 min. Other authors have reported similar results [5,15,50,[56][57][58][59][60][61][62][63][64][65][66].…”
Section: Role In General Surgerysupporting
confidence: 80%
“…Therefore, an adjusted operative technique using minimal and gentle movements is required. In Children's Hospital Zagreb the first TULAA was performed in late 2004 [25], and since mid-2005, TULAA has been our first choice for uncomplicated appendicitis and interval appendectomies. In our series, the mean operative time is shorter in the TULAA group (p = 0.014).…”
Section: Discussionmentioning
confidence: 99%